Effect of Spacing on Survival and Growth Performance of Eucalyptus grandis Hill ex Maiden at Holeta Research Site, Central Ethiopia - Tinsae Bahru; Negash Eshete; Zewdie Woldemariam (International Journal of Forestry Research)
Application of optimum initial plant spacing is one of the most important silvicultural practices to maximize the survival and growth performance of established plants at field. A field experiment was conducted to evaluate the effect of different plant spacing on survival and growth parameters of E. grandis at the ages of 4, 17, 34, 56, 66, and 79 months after establishment at Holeta Research Site. The experimental trail was planted at the initial plant spacings of 1.5 m × 1.5 m, 2 m × 2 m, 2.5 m × 2.5 m, and 3 m × 3 m using a randomized complete block design (RCBD) in three replicates. Other than regular management intervention including regular spot hoeing, weeding, and cleaning, the experiment did not receive any other treatment applications. Evaluation was made on survival and growth performance (plant RCD, height, and DBH) at different ages from 4 to 79 months after planting. Except survival percentage, all other variables (plant RCD, height, and DBH) were significantly affected by initial plant spacing. At the age of 56, 66, and 79 months after planting, the closer plant spacing (2 m × 2 m) was most promising in producing optimum plant height and DBH. Overall, our finding confirmed that initial plant spacing has a significant effect on growth performance of E. grandis at Holeta trail site. Evaluation of basic wood properties in relation with spacing or stand density management for quality wood and wood-based production and clear bole formation is suggested.